The adaptations of midwives after maternal deaths at a tertiary hospital complex in Limpopo Province - Ngoatle, Charity (University of Limpopo, 2015)
The aim of this study was to determine the adaptations of midwives to their work after maternal deaths at a tertiary hospital complex in Limpopo Province. Qualitative phenomenological, exploratory, descriptive and contextual research design was used. Snowball sampling was used to select 22 midwives who experienced maternal deaths. Semi-structured interviews with a guide and audiotape were used to collect data. Tesch’s eight steps of qualitative data analysis were adopted. The study revealed that the midwives had traumatic experiences after maternal deaths and were failing to adapt to their work. Strategies to enhance the adaptation of midwives to their work after maternal death were developed. The study recommends that support, debriefing session, group therapy and counselling should be provided to the affected midwives. There should be provision of adequate number of midwives and material resources in the maternity units to maintain acceptable midwifery care. Sufficient number of midwives should be trained for advanced midwifery to increase capacity in the maternity units. Keywords: Adaptations, midwives, maternal deaths, tertiary hospital
Thesis (M.Sc. (Nursing)) -- University of Limpopo, 2016
Keywords: Midwives; Maternal deaths; Limpopo Province; Adaptation -- Psychology; Midwives -- South Africa -- Limpopo